Deficiency of autism susceptibility gene Trio in cerebellar Purkinje cells leads to delayed motor impairments - Wang, Jinxin; Li, Yimeng; Zhang, Dai; Sun, Wenzhi; Li, Jun (Frontiers in Psychiatry, 2025)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by social interaction deficits, restricted interests and repetitive behaviors. The co-occurrence of motor impairments exacerbates the severity and societal impact of ASD, but the underlying mechanism remains to be elucidated. Research on the comorbidities of ASD including motor impairments could benefit in the life quality improvement in patients with ASD. Here we aimed at investigating the motor behaviors in mice with Trio deletion in Purkinje cells (PCs), and further exploring the cellular and molecular mechanisms. The protein level of Calbindin as PCs’ marker was determined. Behaviors including spontaneous locomotion activity, rotarod, beam balance and gait were tested in mice with the ages of 12-week and 20-week. Magnetic resonance imaging (MRI) scanning with T2 and DTI sequencing was performed in 12-week old mice. Although Triofl/fl; Pcp2-Cre mice showed significant impairments of spontaneous locomotion activity in both 12-week and 20-week ages, only the 20-week but not 12-week Triofl/fl; Pcp2-Cre mice showed extra mild abnormal motor, fine motor coordination, and gait. The decreased expression of Calbindin existed in both 12-week and 20-week old mice compared with control. Differentially expressed genes analysis from RNA-Seq and Gene Co-expression Network Analysis (GCNA) showed that Syne1 and its co-expressed genes were upregulated in Triofl/fl; Pcp2-Cre mice compared to controls. In addition, abnormal ADC values suggested the long-term chronic damage in the cerebellum. Together, our findings indicate that the motor dysfunction in ASD are affected by Trio deletion in PCs with delayed in onset, accompanied with alterations in MRI, histological, and epigenetic level.